Experimental studies on adsorption of malachite green dye by sugarcane bagasse. (2016) - Sharma, Nilay; Agarwal, G.K.; Nandi, Barun Kumar
In the present work, the feasibility of using sugarcane bagasse for the malachite green dye adsorption from aqueous solution has been investigated as low cost and eco-friendly adsorbent. Adsorption studies were conducted on a batch process, to study the effects of contact time, initial dye concentration, adsorbent dose, pH and temperature on dye removal. Maximum colour removal was observed at pH 7. The equilibrium data was analysed by the Langmuir and Freundlich isotherms. The data fitted well with the Langmuir model, with a maximum adsorption capacity of 189.99 mg/g. The pseudo-second-order kinetics was the best for the dye adsorption with good correlation. The experimental results suggest that sugarcane bagasse is a potential low-cost adsorbent for the malachite green dye removal from synthetic dye wastewater. Finally, a process design calculation is also reported to know the amount of adsorbent required for efficient removal of dye from aqueous medium.